2000
DOI: 10.1007/s002960000054
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine ototoxicity in a patient with rheumatoid arthritis

Abstract: We report a case of reversible sensorineural hearing loss due to hydroxychloroquine (HQ) treatment. The patient was a 34-year-old woman with 1 year of rheumatoid arthritis (RA). She developed reversible hearing loss after 5 months of HQ treatment. Sensorineural deafness has previously been reported with chloroquine treatment, but this is the first report of ototoxicity associated with HQ in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 0 publications
2
59
1
3
Order By: Relevance
“…This result agrees with those of other studies which found no correlation between hearing threshold and age, organ system involvement, SLE duration or SLE severity. 1,4,12,16,17,20 However, this may be due to the Our study patients were enrolled at a younger age than those of previously reported studies; however, at 10-year follow up our patients' mean age was similar to that of patients reported earlier (Table III). Considering the age of our patients, it would be reasonable to exclude the effect of some inner ear disorders, such as age-related hearing loss (presbycusis) and long-term exposure to environmental noise (e.g.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This result agrees with those of other studies which found no correlation between hearing threshold and age, organ system involvement, SLE duration or SLE severity. 1,4,12,16,17,20 However, this may be due to the Our study patients were enrolled at a younger age than those of previously reported studies; however, at 10-year follow up our patients' mean age was similar to that of patients reported earlier (Table III). Considering the age of our patients, it would be reasonable to exclude the effect of some inner ear disorders, such as age-related hearing loss (presbycusis) and long-term exposure to environmental noise (e.g.…”
Section: Discussioncontrasting
confidence: 44%
“…20 Nevertheless, Compadretti et al 7 reported the case of a patient who received hydroxychloroquine therapy for three years but did not show any signs of cochlear damage.…”
Section: Discussionmentioning
confidence: 97%
“…Possible explanations of SNHL are immune complex-mediated vasculitis of the inner ear caused by autoantibodies, damaging effects of neuritis to the cochlear nerve caused by the disease itself, and ototoxic side effects of some of the therapeutic drugs [6,11,27]. In our patient population the absence of ototoxic medication use, presence of normal TEOAE responses and absence of reflex decay makes ototoxicity and cochlear nerve involvement unlikely; suggesting involvement of the cochlea due to disease related factors to play the primary role in high frequency SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Seçkin (17) relata um caso de ototoxicidade com HCQ em paciente com AR na dose de 400mg/dia por cinco meses, desenvolvendo disacusia neurossensorial leve bilateral e zumbidos. Após interrupção do tratamento apresentou melhora dos zumbidos em duas semanas e o audiograma retornou ao normal em dois meses.…”
Section: Manifestações Clínicasunclassified